Opinion Dynamics With Cross-Coupling Topics: Modeling and Analysis - Ahn, Hyo-Sung; Ye, Mengbin; Tran, Quoc Van; Trinh, Minh Hoang; Liu, Ji; Moore, Kevin L (IEEE, 2020)
To model the cross couplings of multiple topics, we develop a set of rules for opinion updates of a group of agents. The rules are used to design or assign values to the elements of weighting matrices. The cooperative and anticooperative couplings are modeled in both the inverse-proportional and proportional structures. The behaviors of opinion dynamics are analyzed using a nullspace property of the state-dependent matrix-weighted Laplacian matrices and a Lyapunov candidate. Various consensus properties of the state-dependent matrix-weighted Laplacian matrices are predicted according to the interagent network topology and interdependent topical coupling topologies.